Determination of Early Neurological Outcome by ASIA score following Delayed Anterior Decompression and Stabilization of Lower Cervical Spine Injury - Haque, Mohammed Ashraful; Hossain, SK Sader; Rahman, Md Mahfuzur; Islam, Md Rafiqul; Kadir, Sadika; Sagir, Golam; Hasanat, Md Aminul (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Surgical management of lower cervical spine injury is a very important issue among these patients. Objective: The purpose of the present study was todetermine the early neurological outcome of delayed anterior decompression and stabilization of lower cervical spine injury. Methodology: This cross sectional study was carried out in the Department of Neurosurgery at Dhaka Medical College and Hospital, Dhaka, Bangladesh within the period of January 2010 to July 2011 for a period of one year and 6 months. Neurological outcome following anterior decompression and stabilization of lower cervical spine injury was observe. Patients presented with lower cervical spine injury were included in this prospective study. Quantification of neurologic deficit in lower cervical spine injury patients were carried out by following The American Spinal Injury Association (ASIA) impairment scale. Early neurological outcome was also assessed after operation by using ASIA impairment scale in the follow up period at one, three and six months interval. Result: A total of 31 patients were included in this study. Based on the ASIA impairment scale, preoperatively, 6.4 5% of the injuries were grade A, 16.13 % of the injuries were Grade B, 16.13% of the injuries were Grade C and 35.48 % of the injuries were Grade D. early post-operative complications include dysphagia in 3 5.48% cases, donor site infection in 9.67% cases, CSF leak in 3.22%; catheter related urinary tract infection 9.67% and bed sore occurred in 6.45% cases. Conclusion: In conclusion significant neurological recovery can be expected following delayed anterior decompression and stabilization of lower cervical spine in lower cervical spine injury patient. Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 82-86